Preparation method of BN-confined noble metal composite material

CN118594585BActive Publication Date: 2026-10-30XIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410413058.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-08
Publication Date
2026-10-30
Estimated Expiration
2044-04-08

AI Technical Summary

Technical Problem

[0007]本发明的目的是提供一种BN限域贵金属复合材料的制备方法,解决了现有技术中BN/贵金属颗粒复合材料中贵金属尺寸不可控、易泄露和循环使用效果不佳的问题

Benefits of technology

[0030]一种BN限域贵金属复合材料的制备方法,首先将荷负电聚合物与贵金属纳米颗粒组装,通过微波干燥法辅助得到了尺寸可控、光热性能良好的功能化贵金属纳米颗粒;通过冷冻干燥协同闪烧处理得到的类“丝瓜络”状BN纤维笼,凸显了BN的吸附性能,有效增强催化剂的吸附能力;同时通过射频溅射技术将功能化贵金属纳米颗粒射入类“丝瓜络”状的BN纤维笼中,使得内部颗粒限域存在,避免了催化后的膨大溶出、催化效率降低;同时催化还原后的4-氨基苯酚能结合修饰功能化贵金属纳米颗粒,形成具有优异抗菌性能的复合体,使得催化剂在催化后再次拥有广泛的抗菌谱和强大的抗菌效果,达到循环使用后的催化剂和催化产物共回收、共利用变为可用再生资源的效果,这使得催化剂循环效能高、绿色可持续发展性能好,在污水处理、空气净化、抗菌杀毒等领域有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118594585B_ABST
    Figure CN118594585B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of BN confined noble metal composite material. First, a negatively charged polymer is assembled with noble metal nanoparticles to obtain functionalized noble metal nanoparticles with controllable size and good photo-thermal performance by a microwave drying method. A "silk gourd reticulation" like BN fiber cage is obtained by freeze drying and flash processing, which effectively enhances the adsorption capacity of the catalyst. At the same time, the functionalized noble metal nanoparticles are shot into the BN fiber cage by radio frequency sputtering technology, so that the internal particles exist in confinement, avoiding swelling and dissolution after catalysis and reducing the catalytic efficiency. At the same time, the functionalized noble metal nanoparticles are combined with 4-amino phenol after catalytic reduction to form a composite with excellent antibacterial performance, so that the catalyst has excellent antibacterial performance after catalysis, achieving the effect of co-recovery and co-utilization of waste catalyst and catalytic product into available renewable resources, and having wide application prospects in the fields of sewage treatment, air purification, antibacterial and disinfection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst preparation, specifically relating to a method for preparing a BN-confined noble metal composite material. Background Technology

[0002] Taking p-nitrophenol (PNP) as an example, it is widely used in the production of pharmaceuticals, dyes, pesticides, herbicides, and fungicides. These compounds have long residual periods in the environment, causing serious harm to soil and plants. Therefore, wastewater containing PNP must be pretreated before being discharged into the ecosystem. Studies have shown that adsorption-coupled catalysis can effectively remove PNP from the environment because the adsorbent material can rapidly capture PNP, thus promoting the degradation of PNP by the catalyst. Among many adsorbent materials, boron nitride (BN) has attracted widespread attention from researchers due to its graphene-like structure and many remarkable properties, such as high surface area, high-temperature oxidation resistance, and high chemical stability. Therefore, BN-based materials have satisfactory adsorption capacity for inorganic pollutants (such as heavy metal ions) and organic pollutants (such as dyes and drug molecules). However, many problems exist in its use, such as unstable adsorption effects, good adsorption but weak catalysis, and non-reusability.

[0003] Liu et al. (Liu Z, Zhao K, Li D, et al. Pore size regulation of BN fibers and its effect on tetracycline adsorption[J]. Journal of the American Ceramic Society, 2023, 106(12): 7803-7811.) prepared BN fibers with a hierarchical micro-mesoporous structure through in-situ synthesis and two-step calcination of precursors. The obtained hierarchical porous BN fibers achieved a maximum adsorption capacity of 870.29 mg / g for tetracycline, a typical antibiotic, which is more than twice that reported in the existing literature (438 mg / g). Although the prepared porous BN fibers have strong adsorption performance, this is the only limitation, and they cannot degrade pollutants on their own.

[0004] Studies have shown that noble metal nanoparticles combined with boron nitride (BN) can catalyze the degradation of pollutants and inhibit bacterial contamination in aquatic bodies, which is of positive significance for the rapid degradation of pollutants in water. For example, Zhang Yumei et al. (Zhang Yumei, Gao Tong, Wang Yue et al. Study on the efficient reduction of p-nitrophenol by modifying porous boron nitride with copper nanoparticles [J]. Journal of Hebei University of Science and Technology, 2024, 45(01): 59-66.) successfully loaded Cu nanoparticles onto the surface of h-BN using CuCl2·2H2O as the copper source and porous h-BN with a large specific surface area as the support through a simple liquid-phase reduction method. The synthesized Cu / h-BN has a large surface area, providing sufficient active sites for the catalytic reaction and exhibiting good catalytic performance. However, the 4-aminophenol formed after Cu nanoparticles catalyze the reduction of 4-nitrophenol quickly leaves the catalyst surface and dissolves in water, which may cause re-contamination. Furthermore, the catalyst cannot be recycled after use, resulting in low catalyst cycle efficiency. At the same time, it was found that the size of CuNPs particles increased after catalysis, leading to particle desorption and reduced catalytic performance. Therefore, the size control of CuNPs particles is also an important research issue.

[0005] Although this invention also proposes a superparamagnetic small-sized alloy nanoparticle and its preparation method in the Chinese patent "A Superparamagnetic Small-Sized Alloy Nanoparticle and its Preparation Method" (application number: CN202010921430.2, authorization number: CN112108645B, announcement date: 2022.07.08), the alloy nanoparticles are Co-Pt alloy nanoparticles with small particle size, high saturation magnetization, and strong oxidation and corrosion resistance, overcoming the limitation of traditional catalysts that cannot be recycled and reused, this invention cannot break the situation of low catalyst recycling efficiency and weak sustainable development by relying solely on the recycling and reuse of a single catalyst, and the size control of nanoparticles is also an issue that needs attention.

[0006] A similar Chinese patent, "A Phytic Acid Metal Complex Catalyst and Its Preparation Method and Application" (Application No.: CN202211430827.7, Authorization No.: CN115739190B, Publication Date: 2024.02.13), also invented a phytic acid metal complex catalyst including iron phytate. In the synthesis of benzoxazole and benzothiazole derivatives, it uses 2-nitrophenol or its derivatives, 2-aminobenzylthiol, and benzyl alcohol or its derivatives as reactants, replacing strong oxidants and unstable aldehydes. Furthermore, this complex, as a heterogeneous catalyst, can be recycled and reused up to five times without significantly reducing its catalytic activity, and exhibits broad tolerance to benzyl alcohol and 2-nitrophenol derivatives, making it a highly efficient heterogeneous catalyst. However, as a catalyst, it still has significant shortcomings in terms of recycling efficiency and industrial sustainability. Summary of the Invention

[0007] The purpose of this invention is to provide a method for preparing BN-confined noble metal composite materials, which solves the problems of uncontrollable noble metal size, easy leakage, and poor recycling effect in existing BN / noble metal particle composite materials.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a BN-confined noble metal composite material is specifically implemented according to the following steps:

[0010] Step 1: Preparation of functionalized noble metal nanoparticle precursors

[0011] The noble metal nanoparticle precursor and the negatively charged polymer were added to a solvent, heated and stirred in a water bath, and then centrifuged after being mixed evenly to obtain the functionalized noble metal nanoparticle precursor.

[0012] Step 2, Microwave drying treatment

[0013] The functionalized noble metal nanoparticle precursor obtained in step 1 was subjected to microwave drying to obtain functionalized noble metal nanoparticles.

[0014] Step 3, prepare the modified BN mixture.

[0015] The negatively charged polymer, nitrogen source, and boron source were added to the solvent, heated in a water bath and stirred until homogeneous, and then frozen and stored to obtain a modified BN mixture.

[0016] Step 4, freeze-drying

[0017] The modified BN mixture obtained in step 3 was freeze-dried to obtain the modified BN precursor.

[0018] Step 5, Radio Frequency Sputtering Process

[0019] The functionalized noble metal nanoparticles obtained in step 2 were filled into the modified BN precursor obtained in step 4 by radio frequency sputtering technology to obtain the final catalyst precursor.

[0020] Step 6, flash burn treatment

[0021] The catalyst precursor obtained in step 5 is subjected to flash calcination. After flash calcination, the modified BN precursor becomes modified BN fiber, and finally a catalyst with modified BN fiber encapsulating functionalized noble metal nanoparticles is obtained, which is a BN confined noble metal composite material.

[0022] Further, in step 1, the noble metal nanoparticle precursor is any one of chloroauric acid, silver nitrate, chloroplatinic acid, and palladium chloride; the negatively charged polymer is any one of phytic acid, polyacrylic acid, polyacrylamide, and sodium polyacrylate; the solvent is a mixed solution of water and any one or more of anhydrous ethanol, DMF, acetone, and acetic acid, wherein water accounts for more than 50% of the total mass of the solvent; the water bath heating parameters are: water bath temperature of 80-90℃, water bath time of 2-3h; and the centrifugation parameters are: centrifugation speed of 10000-12000rpm, centrifugation time of 10-15min.

[0023] Furthermore, the mass ratio of the noble metal nanoparticle precursor to the negatively charged polymer is 1:5 to 3:4.

[0024] Furthermore, the microwave drying parameters in step 2 are: microwave frequency 300-500MHz, drying time 10-15min.

[0025] Further, in step 3, the negatively charged polymer is any one of phytic acid, polyacrylic acid, polyacrylamide, and sodium polyacrylate; the nitrogen source is any one of urea, ammonia, and melamine; the boron source is any one of methyl borate, boric acid, and ammonium borate; the solvent is water; the water bath heating parameters are: water bath heating temperature of 80℃~90℃, heating time of 4h~6h; and the freezing storage conditions are: below -25℃.

[0026] Furthermore, the process parameters for freeze-drying in step 4 are as follows: freezing temperature is -60℃ to -80℃, pressure is 0.05mbar to 0.12mbar, and freeze-drying time is more than 15 minutes.

[0027] Furthermore, the process parameters for RF sputtering in step 5 are: sputtering temperature 200-400℃, argon flow rate 3-6 ml / min, sputtering time 30-40 min, and sputtering power 300-400 W.

[0028] Furthermore, the process parameters for the flash burning treatment in step 6 are: furnace temperature 600℃~700℃, electric field strength 8KV / CM~10KV / CM, limiting current 200MA~300MA, and constant current state 120s~150s.

[0029] Compared with the prior art, the beneficial effects of the present invention are:

[0030] A method for preparing a BN-confined noble metal composite material involves first assembling a negatively charged polymer with noble metal nanoparticles, and then obtaining functionalized noble metal nanoparticles with controllable size and good photothermal properties through microwave drying. A "loofah-like" BN fiber cage obtained through freeze-drying combined with flash calcination highlights the adsorption performance of BN and effectively enhances the catalyst's adsorption capacity. Simultaneously, functionalized noble metal nanoparticles are injected into the "loofah-like" BN fiber cages using radio frequency sputtering technology, ensuring the internal particle confinement and preventing post-catalytic expansion, dissolution, and reduced catalytic efficiency. Furthermore, the catalytically reduced 4-aminophenol can combine with the modified functionalized noble metal nanoparticles to form a composite with excellent antibacterial properties. This allows the catalyst to retain a broad antibacterial spectrum and strong antibacterial effect after catalysis, achieving the effect of co-recovery and co-utilization of the catalyst and catalytic products into usable renewable resources. This results in high catalyst recycling efficiency and good green and sustainable development performance, with broad application prospects in wastewater treatment, air purification, and antibacterial disinfection. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the morphology of the catalyst particles prepared in Example 1 of the present invention.

[0032] In the attached figure, 1-modified BN fiber, 2-functionalized noble metal nanoparticles. Detailed Implementation

[0033] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0034] A method for preparing a BN-confined noble metal composite material is specifically implemented according to the following steps:

[0035] Step 1: Preparation of functionalized noble metal nanoparticle precursors

[0036] A noble metal nanoparticle precursor and a negatively charged polymer in a ratio of 1:5 to 3:4 are dissolved in a solvent and heated in a water bath with stirring until homogeneous. The water bath temperature is 80–90°C, and the water bath time is 2–3 hours. The resulting functionalized noble metal nanoparticle precursor solution is then centrifuged at 10,000–12,000 rpm for 10–15 minutes. The noble metal nanoparticle precursor is any one of the precursors capable of synthesizing antibacterial metal nanoparticles, such as chloroauric acid, silver nitrate, chloroplatinic acid, and palladium chloride. The negatively charged polymer is any one of the negatively charged conductive polymers, such as phytic acid, polyacrylic acid, polyacrylamide, and sodium polyacrylate. The solvent is a mixture of water and any one or more of anhydrous ethanol, DMF, acetone, and acetic acid, with water accounting for more than 50% of the total solvent mass.

[0037] Step 2, Microwave drying treatment

[0038] The functionalized noble metal nanoparticle precursor obtained in step 1 was subjected to microwave drying to obtain functionalized noble metal nanoparticles. The specific parameters for microwave drying were: microwave frequency 300-500MHz and drying time 10-15min.

[0039] Step 3, prepare the modified BN mixture.

[0040] The negatively charged polymer, nitrogen source, and boron source are added to a solvent and heated in a water bath at 80℃~90℃ for 4h~6h to obtain a modified BN mixture, which is then frozen and stored below -25℃. The nitrogen source can be any nitrogen-containing compound such as urea, ammonia, or melamine; the boron source can be any boron-containing compound such as methyl borate, boric acid, or ammonium borate; and the solvent is an appropriate amount of water.

[0041] Step 4, freeze-drying

[0042] The modified BN mixture obtained in step 3 was subjected to freeze-drying. The freeze-drying process parameters were: freezing temperature of -60℃ to -80℃, pressure of 0.05mbar to 0.12mbar, and freeze-drying time of more than 15 minutes, finally obtaining the modified BN precursor.

[0043] Step 5, Radio Frequency Sputtering Process

[0044] The functionalized noble metal nanoparticles obtained in step 2 were filled into the modified BN precursor obtained in step 4 by radio frequency sputtering technology. The sputtering temperature was 200-400℃, the argon flow rate was 3-6 ml / min, the sputtering time was 30-40 min, and the sputtering power was 300-400 W, thus obtaining the catalyst precursor.

[0045] Step 6, flash burn treatment

[0046] The catalyst precursor treated in step 5 was subjected to flash calcination at a furnace temperature of 600℃~700℃, an electric field strength of 8KV / CM~10KV / CM, a limiting current of 200MA~300MA, and a constant current state for 120s~150s. After flash calcination, the modified BN precursor became modified BN fibers, and finally a catalyst with modified BN fibers encapsulating functionalized noble metal nanoparticles was obtained, which is the BN confined noble metal composite material.

[0047] This invention selects positively charged noble metal nanoparticles with antibacterial properties and negatively charged polymers to electrostatically assemble composite nanoparticles. The ratio of 1:5 to 3:4 is determined based on charge balance and size. If the ratio differs too much, it will lead to charge imbalance. Due to the electrostatic interaction of "like charges repel, unlike charges attract," the nanoparticles cannot be uniformly dispersed in the liquid phase or effectively assembled, and the size of the composite nanoparticles cannot be controlled. In addition, the negatively charged polymer is filled into the "loofah"-like BN fibers. This is to increase the actual sintering temperature of the catalyst during flash calcination by utilizing the conductivity of the polymer, which helps to rapidly form BN fibers. The polymer decomposes during the flash calcination stage without affecting the performance of the catalyst itself. The selection of noble metal nanoparticles with antibacterial properties can not only achieve the effect of catalytic reduction of 4-nitrophenol, but also coexist and combine amicably with the catalytic product 4-aminophenol. Furthermore, the combined composite particles have excellent antibacterial properties, enabling further recycling and reuse of the catalyst.

[0048] Example 1

[0049] First, chloroauric acid and phytic acid were dissolved in water and acetone in a 1:5 ratio. The mixture was then synthesized in a one-pot bath at 80°C for 2 hours. The resulting functionalized Au precursor solution was centrifuged at 10,000 rpm for 10 minutes to obtain the functionalized Au precursor.

[0050] The obtained functionalized Au precursor was subjected to microwave drying at a frequency of 300 MHz for 10 min to obtain functionalized Au nanoparticles.

[0051] Phytic acid, melamine, and boric acid were added to water, heated in a water bath at 80°C for 4 hours, and then frozen and stored at -25°C to obtain a modified BN mixture.

[0052] The obtained modified BN mixture was freeze-dried at a temperature of -60℃ and a pressure of 0.05 mbar for 15 minutes to finally obtain the modified BN precursor.

[0053] Functionalized Au nanoparticles were filled into a modified BN precursor using radio frequency sputtering technology. The sputtering temperature was 200℃, the argon flow rate was 3ml / min, the sputtering time was 30min, and the sputtering power was 300W, finally obtaining the BN@Au catalyst precursor.

[0054] The BN@Au catalyst precursor was subjected to flash calcination at a furnace temperature of 600℃, an electric field strength of 8KV / CM, a limiting current of 200MA, and a constant current state for 120s to obtain the BN@Au catalyst.

[0055] Figure 1This is a schematic diagram of the morphology of the catalyst prepared in Example 1 of the present invention. From... Figure 1 It can be seen that the modified BN after freeze-drying and flash calcination formed a "loofah"-like structure, with the internal functionalized noble metal nanoparticles well fixed inside the hollow tube.

[0056] Example 2

[0057] First, silver nitrate and polyacrylic acid in a 3:4 ratio were dissolved in water and acetic acid, and the mixture was synthesized in a one-pot bath at 90°C for 3 hours. Then, the functionalized Ag precursor solution was centrifuged at 12,000 rpm for 15 minutes to obtain the functionalized Ag precursor.

[0058] The functionalized Ag precursor was then subjected to microwave drying at a frequency of 400 MHz for 15 min to obtain functionalized Ag nanoparticles.

[0059] Polyacrylic acid, melamine, and ammonium borate were added to water and heated in a water bath at 90°C for 6 hours. The mixture was then frozen and stored at -35°C to obtain a modified BN mixture.

[0060] The obtained modified BN mixture was freeze-dried at -80℃ and 0.12 mbar for 20 minutes to obtain the modified BN precursor.

[0061] Functionalized Ag nanoparticles were filled into a modified BN precursor using radio frequency sputtering technology at a sputtering temperature of 400℃, an argon flow rate of 6 ml / min, a sputtering time of 40 min, and a sputtering power of 400 W, ultimately yielding a BN@Ag catalyst precursor.

[0062] The BN@Ag catalyst precursor was subjected to flash calcination at a furnace temperature of 700℃, an electric field strength of 10KV / CM, a limiting current of 300MA, and a constant current state for 150s to obtain the BN@Ag catalyst.

[0063] Example 3

[0064] First, chloroplatinic acid and sodium polyacrylate in a 1:2 ratio were dissolved in water and DMF, and synthesized in a one-pot bath at 80°C for 2 hours. The resulting functionalized Pt precursor solution was then centrifuged at 10,000 rpm for 15 minutes to obtain the functionalized Pt precursor.

[0065] The functionalized Pt precursor was then subjected to microwave drying at a frequency of 350 MHz for 12 min to obtain functionalized Pt nanoparticles.

[0066] Sodium polyacrylate, urea, and methyl borate were added to water and heated in a water bath at 90°C for 6 hours. After freezing and storing at -25°C, a modified BN mixture was obtained.

[0067] The obtained modified BN mixture was freeze-dried at a temperature of -70℃ and a pressure of 0.10 mbar for 20 minutes to finally obtain the modified BN precursor.

[0068] Functionalized Pt nanoparticles were filled into a modified BN precursor using radio frequency sputtering technology at a sputtering temperature of 350℃, an argon flow rate of 5 ml / min, a sputtering time of 35 min, and a sputtering power of 350 W, ultimately yielding a BN@Pt catalyst precursor.

[0069] The BN@Pt catalyst precursor was subjected to flash calcination at a furnace temperature of 650℃, an electric field strength of 9KV / CM, a limiting current of 250MA, and a constant current state for 140s to obtain the BN@Pt catalyst.

[0070] Example 4

[0071] First, palladium chloride and polyacrylamide in a 1:4 ratio were dissolved in water and anhydrous ethanol, and synthesized in a one-pot bath at 80°C for 2 hours. The resulting functionalized Pb precursor solution was then centrifuged at 11,000 rpm for 13 minutes to obtain the functionalized Pb precursor.

[0072] The functionalized Pb precursor was then subjected to microwave drying at a frequency of 500 MHz for 14 min to obtain functionalized Pb nanoparticles.

[0073] Polyacrylamide, ammonia, and methyl borate were added to water, heated in a water bath at 90°C for 6 hours, and then frozen and stored at -40°C to obtain a modified BN mixture.

[0074] The obtained modified BN mixture was freeze-dried at a temperature of -75°C, a pressure of 0.11 mbar, and a time of 20 minutes to finally obtain the modified BN precursor.

[0075] Functionalized Pb nanoparticles were filled into the modified BN precursor using radio frequency sputtering technology at a sputtering temperature of 350℃, an argon flow rate of 4 ml / min, a sputtering time of 40 min, and a sputtering power of 370 W, ultimately yielding the BN@Pb catalyst precursor.

[0076] The BN@Pb catalyst precursor was subjected to flash calcination at a furnace temperature of 700℃, an electric field strength of 10KV / CM, a limiting current of 250MA, and a constant current state for 150s to obtain the BN@Pb catalyst.

Claims

1. A method for preparing a BN-confined noble metal composite material, characterized in that, The specific steps are as follows: Step 1: Preparation of functionalized noble metal nanoparticle precursors The noble metal nanoparticle precursor and the negatively charged polymer were added to a solvent, heated and stirred in a water bath, and then centrifuged after being mixed evenly to obtain the functionalized noble metal nanoparticle precursor. Step 2, Microwave drying treatment The functionalized noble metal nanoparticle precursor obtained in step 1 was subjected to microwave drying to obtain functionalized noble metal nanoparticles. Step 3, prepare the modified BN mixture. The negatively charged polymer, nitrogen source, and boron source were added to the solvent, heated in a water bath and stirred until homogeneous, and then frozen and stored to obtain a modified BN mixture. Step 4, freeze-drying The modified BN mixture obtained in step 3 was freeze-dried to obtain the modified BN precursor. Step 5, Radio Frequency Sputtering Process The functionalized noble metal nanoparticles obtained in step 2 were filled into the modified BN precursor obtained in step 4 by radio frequency sputtering technology to obtain the final catalyst precursor. Step 6, flash burn treatment The catalyst precursor obtained in step 5 is subjected to flash calcination. After flash calcination, the modified BN precursor becomes modified BN fiber, and finally a catalyst with modified BN fiber encapsulating functionalized noble metal nanoparticles is obtained, which is a BN confined noble metal composite material.

2. The method for preparing a BN-confined noble metal composite material according to claim 1, characterized in that, The noble metal nanoparticle precursor in step 1 is any one of chloroauric acid, silver nitrate, chloroplatinic acid, and palladium chloride; the negatively charged polymer is any one of phytic acid, polyacrylic acid, and sodium polyacrylate; the solvent is a mixed solution of water and any one or more of anhydrous ethanol, DMF, acetone, and acetic acid, wherein water accounts for more than 50% of the total mass of the solvent; the water bath heating parameters are: water bath temperature of 80-90℃, water bath time of 2-3h; and the centrifugation parameters are: centrifugation speed of 10000-12000rpm, centrifugation time of 10-15min.

3. The method for preparing a BN-confined noble metal composite material according to claim 2, characterized in that, The mass ratio of the noble metal nanoparticle precursor to the negatively charged polymer is 1:5 to 3:

4.

4. The method for preparing a BN-confined noble metal composite material according to claim 1, characterized in that, The microwave drying parameters in step 2 are: microwave frequency 300-500MHz, drying time 10-15min.

5. The method for preparing a BN-confined noble metal composite material according to claim 1, characterized in that, In step 3, the negatively charged polymer is any one of phytic acid, polyacrylic acid, and sodium polyacrylate; the nitrogen source is any one of urea, ammonia, and melamine; the boron source is any one of methyl borate, boric acid, and ammonium borate; the solvent is water; the water bath heating parameters are: water bath heating temperature of 80℃~90℃, heating time of 4h~6h; and the freezing storage conditions are: below -25℃.

6. The method for preparing a BN-confined noble metal composite material according to claim 1, characterized in that, The process parameters for freeze drying in step 4 are: freezing temperature of -60℃ to -80℃, pressure of 0.05mbar to 0.12mbar, and freeze drying time of more than 15 minutes.

7. The method for preparing a BN-confined noble metal composite material according to claim 1, characterized in that, The process parameters for RF sputtering in step 5 are: sputtering temperature 200-400℃, argon flow rate 3-6mL / min, sputtering time 30-40min, and sputtering power 300-400W.

8. The method for preparing a BN-confined noble metal composite material according to claim 1, characterized in that, The process parameters for the flash burning treatment in step 6 are: furnace temperature 600℃~700℃, electric field strength 8KV / CM~10KV / CM, limiting current 200MA~300MA, and constant current state 120s~150s.

Citation Information

Patent Citations

  • Superparamagnetic small-sized alloy nanoparticles and their preparation method

    CN112108645B

  • A phytic acid metal complex catalyst and its preparation method and application

    CN115739190B

  • Nano composite material synthesis device based on instantaneous high-temperature Joule thermal method, preparation method and application

    CN113578222A

  • Nickel / nickel boron / hexagonal boron nitride composite material and preparation method and application thereof

    CN116706168A